Early career mathematics teachers: Concepts, methods, and strategies for comparative international research. (November 2020) - Tatto, Maria Teresa; Rodriguez, Michael C.; Reckase, Mark
Abstract: In this article, we report on the challenges entailed in the development of concepts, methods, and strategies for designing and implementing a cross-national research study of the first-years of school-mathematics teaching, including an exploration of how beginning mathematics teachers differ in their preparation, knowledge for teaching, teaching practice, working conditions, and pupil characteristics. The study was designed as a proof-of-concept for a study of teaching and teacher education to be implemented by educationalists, teacher educators, and early career teachers as an ongoing professional endeavor. Primary among the challenges was the development of the sampling design and the construction of measures. Highlights: We present results of a Proof-of-Concept Study to research Early Career Mathematics Teaching cross-nationally. We studied how beginning mathematics teachers differ in their knowledge, teaching practice, and working conditions. We developed knowledge assessments and questionnaires for primary and secondary teachers, plus teacher observations. We developed a sampling frame to draw representative samples of early career mathematics teachers. Our data provide validity evidence of measures, warranting taking methods to scale.